Role Clarity, Satisfaction with Internal Communication to Increase Employee Retention through Perceived Organizational Support of Kareb Cooperative Employees in Bojonegoro - Yunta Nur Fauzi; Amiartuti Kusmaningtyas; Sumiati (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2026)
This causal quantitative study aims to examine the effects of Role Clarity and Internal Communication Satisfaction on Employee Retention, with Perceived Organizational Support (POS) serving as a mediating variable among employees of Koperasi KAREB Bojonegoro. The study employed a census sampling technique, involving 98 employees as respondents. Data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) version 4.0. The results indicate that: (1) Role Clarity and Internal Communication Satisfaction have positive and significant effects on Perceived Organizational Support; (2) Perceived Organizational Support has a positive and significant effect on Employee Retention; and (3) Perceived Organizational Support positively and significantly mediates the relationships between Role Clarity, Internal Communication Satisfaction, and Employee Retention. Therefore, management is encouraged to strengthen POS through regularly reviewed Standard Operating Procedures (SOPs), transparent internal communication, and a human-centered managerial approach to sustain employee loyalty and organizational performance